Visual Acuity at Presentation in the Second Eye versus First Eye in Patients with Exudative Age-Related Macular Degeneration. Issue 1 (January 2016) - Chevreaud, Olivier; Semoun, Oudy; Blanco-Garavito, Rocio; Kamami-Levy, Cynthia; Merle, Benedicte; Jung, Camille; Querques, Giuseppe; Souied, Eric H.
Purpose: To assess the difference in best-corrected visual acuity (BCVA) at presentation between the first and second eye in patients with bilateral neovascular age-related macular degeneration (AMD). Methods: We reviewed the charts of all patients who had a clinical examination for neovascular AMD at the University Eye Clinic of Creteil in January 2013. We retrospectively analyzed demographic and clinical data for 264 patients. Results: In the fellow eye, choroidal neovascularization (CNV) developed in 75/264 patients (28.4%) with a time interval between the 2 events of 30.3 months (range 6-145). Data were available on 65 patients: 14/65 (21.5%) were asymptomatic, 24/65 (36.9%) had BCVA >20/40, whereas at the time of CNV diagnosis in the first eye, no patient was asymptomatic (p<0.0001), and 11/65 (16.9%) eyes had BCVA >20/40 (p<0.0001). The mean BCVA of the first affected eye was 0.68 (±0.41) logarithm of minimum angle of resolution (logMAR) and the mean BCVA for the second eye was 0.36 (±0.29) logMAR (p<0.0001). Conclusions: The BCVA at the time of diagnosis of CNV was higher in the second eye than in the first affected eye. This was possibly due to several factors including systematic bilateral examination in follow-up of unilateral exudative AMD that allowed detection of 20% of cases.